A current concern: The consumption of cannabis associated with schizophrenia: Una preocupación en la actualidad: el consumo de cannabis asociado a la esquizofrenia - Ponce Blas, Shirley del Carmen (2019)
The incidence of schizophrenia in developed and considered developing countries ranges from 7 - 14% per 100,000 inhabitants, according to reports to 2019 of the World Health Organization (WHO). Schizophrenia is one of the most serious mental illnesses that exist, affecting the patient's thoughts, will, emotions and social relationships, directly involving their closest relatives. In general, the causes that lead the patient to develop schizophrenia are not known, however, it is known that those patients where family members have suffered from schizophrenia are more predisposed to have it. There are currents that strongly support the theory that there are alterations in the neonatal brain or even before birth that will cause these structural alterations in neurotransmitters, especially in dopamine and serotonin.